Empirical evidence on the resource curse hypothesis in oil abundant economy - Nanthakumar, Loganathan; Saqlain Latif, Satti; Abdul, Farooq (Elsevier, 2014)
This present study investigates the relationship between natural resource abundance and economic growth for Venezuelan economy. We have applied the ARDL bounds testing approach to cointegration developed by Pesaran et al. (2001) to examine its long run relationship amid the variables. The VECM Granger causality is applied to test the direction of causality among the variables. This study covers the period of 1971–2011. Our empirical evidence indicated that variables are found to be cointegrated. The results confirm that natural resource abundance impedes economic growth. Financial development, capital stock and trade openness enhance economic growth. The feedback hypothesis is also found between natural resource abundance and economic growth.